Seriously! : investigating crashes and crises as if women mattered - Enloe, Cynthia H., 1938- (University of California Press, 2013)
In Seriously!, Cynthia Enloe, author of the groundbreaking analysis of globalization, Bananas, Beaches, and Bases, addresses two deeply gendered and contested questions: Who is taken seriously? And who gets to bestow the label ""serious"" on others? With a strategy of taking both women and gender dynamics seriously, Cynthia Enloe investigates the Dominique Strauss-Kahn affair and the banking crash of 2008, the subsequent recession, as well as UN peacekeeping and the ongoing Egyptian revolution. Each case study highlights the gritty experiences of women in diverse circumstances-in banks, on the